Pre-operative and peri operative predictors of acute renal failure after cardiac surgery - Dhaulta, Praveen; Panwar, Vikas (International Journal of Advances in Medicine, 2019)
Background: Acute kidney injury (AKI) is one of the most serious complications during the postoperative period of cardiac surgery. Multiple variables predict the ARF after cardiac surgery. Objective of this study was to evaluate the significance of pre and peri-operative variables which may help in predicting the chances of developing ARF after cardiac surgery. Methods: This study was an observational, prospective study conducted among patients who were scheduled to undergo open heart surgery under cardiopulmonary bypass. Results: In total, 50 patients who underwent open-heart surgery, ARF was seen in 5 patients, with the incidence rate of 10%. Acute renal failure was present in one patient with ejection fraction <35, 2 patients had ejection fraction between 35 to 50 and 2 patients with ejection fraction >50. It was seen in 4 patients with 1-2 hrs of cardiopulmonary bypass and in 1 patient with >2 hrs of cardiopulmonary bypass. ARF was also seen in 4 patients with hematocrit between 22-26% and in 1 patient with >26%. Conclusions: The study provided a clinical variable score that can predict ARF after open-heart surgery. The score enhances the accuracy of prediction by accounting for the effect of all major risk factors of ARF.